The wonder and the mystery 10 years of reflections from the Annals of Family Medicine - Gotler, Robin S. (Radcliffe Publishing, 2013)
The book is a unique collection of personal reflections and ideas from the Annals of Family Medicine, a primary care research journal. Each article has some connection to primary care but, as a compilation, it covers a wide range of topics, from the deeply personal to professional and policy issues. Written by clinicians, researchers and patients, the articles speak with a remarkable honesty, providing inspirational insights into health care and humanity. They shed light on the value of primary care not only as an approach to health care but also the unique and important role it plays in people's lives